Occupational exposure and sinonasal cancer: a systematic review and meta-analysis - Binazzi, Alessandra (BMC Cancer, 2015)
BACKGROUND: Sinonasal cancer (SNC) has been related to occupational exposures, but the relative risk associated to specific jobs and/or carcinogen exposures other than wood and leather dust is generally based on small or inadequate sample sizes and the range of observed estimates is large. This paper is aimed at investigating such relationship through a systematic review of the literature followed by a meta-analysis of studies meeting specific inclusion criteria. METHODS: Systematic search was made with PubMed, Google Scholar and Scopus engines using related keywords. Occupational exposures include wood and leather dust, formaldehyde, nickel and chromium compounds, textile industry, farming and construction. Meta-analysis of published studies after 1985 with a case-control or cohort design was performed, firstly using the fixed-effect model. Heterogeneity was assessed with the Q statistical test and quantified by the I(2) index. When the heterogeneity hypothesis appeared relevant, the random-effect model was chosen. Sources of heterogeneity were explored using subgroup analyses. RESULTS: Out of 63 reviewed articles, 28 (11 cohort, 17 case-control) were used in the meta-analysis. Heterogeneity among studies was observed and random-effects models were used. Exposure to wood dust results associated with SNC (RR(pooled) = 5.91, 95% CI: 4.31-8.11 for the case-control studies and 1.61, 95% CI: 1.10-2.37 for the cohort studies), as well as to leather dust (11.89, 95% CI: 7.69-18.36). The strongest associations are with adenocarcinomas (29.43, 95% CI: 16.46-52.61 and 35.26, 95% CI: 20.62-60.28 respectively). An increased risk of SNC for exposures to formaldehyde (1.68, 95% CI: 1.37-2.06 for the case control and 1.09, 95% CI: 0.66-1.79 for the cohort studies), textile industry (2.03, 95% CI: 1.47-2.8), construction (1.62, 95% CI: 1.11-2.36) and nickel and chromium compounds (18.0, 95% CI: 14.55-22.27) was found. Subset analyses identified several sources of heterogeneity and an exposure-response relationship was suggested for wood dust (p = 0.001). CONCLUSIONS: By confirming the strength of association between occupational exposure to causal carcinogens and SNC risk, our results may provide indications to the occupational etiology of SNC (not only wood and leather dusts). Future studies could be focused on specific occupational groups to confirm causative agents and to define appropriate preventive measures. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-015-1042-2) contains supplementary material, which is available to authorized users.